Beverage‐specific situational norms: Evidence from the Dutch electronic appropriate beverage task. (9th October 2020) - Cook, Megan; Kuntsche, Sandra; Smit, Koen; Voogt, Carmen; Kuntsche, Emmanuel
Abstract: Introduction and Aims: By the time young adolescents initiate alcohol consumption they have firmly established attitudes, expectations and beliefs about alcohol and its effects. To further unravel the origins of this knowledge in childhood, we aim to address Dutch children's knowledge of the types of alcoholic beverages adults typically consume in certain situational contexts (i.e. their knowledge of beverage‐specific situational norms). Design and Methods: A total of 329 children (4–8 years old) completed the Dutch electronic Appropriate Beverage Task at three‐time points (2015, 2016, 2017). Three‐level regression models were estimated examining whether children's beverage‐specific situational norms depend on the gender of the person displayed in the task, sex of the participant and whether there were any beverage‐specific changes over time. Results: Beverage‐specific findings seem to be robust across the appropriateness of the situation. Beer was the most frequently attributed alcoholic beverage overall and across the common drinking situations. White wine was attributed significantly more to females in the task. Beer, red wine and champagne were attributed significantly more to males. Attributions of individual alcoholic beverages did not change significantly over time. There were no significant differences between the participating boys and girls. Discussion and Conclusions: Results suggest that 4–8‐year olds are yet to form knowledge of beverage‐specific situational norms. Independent of the situation, time and participants' sex, the gender of the person displayed in the task seemed to be more salient to children than situational or environmental indicators in determining consumption.